Variation in costs among surgeons and hospitals in Pediatric tympanostomy tube placement. (24th November 2015) - Sjogren, Phayvanh P.; Gale, Craig; Henrichsen, Jacob; Olsen, Griffin; Ott, Mark J.; Peters, Matthew; Srivastava, Rajendu; Meier, Jeremy D.
Abstract : Objectives/Hypothesis: 1) Identify the major expenses for outpatient pediatric tympanostomy tube placement in a multihospital network. 2) Compare differences for variations in costs among hospitals and surgeons. Methods: An observational cohort study in a multihospital network using a standardized activity‐based accounting system to determine hospital costs for tympanostomy tube placement from February 2011 to January 2015. Children aged 6 months to less than 3 years old who underwent same‐day surgery (SDS) for tympanostomy tubes at 15 hospital facilities were included. Subjects with additional procedures were excluded. Hospital costs were subdivided into categories including operating room (OR), SDS preoperative, SDS postoperative, postanesthesia care unit, anesthesia, pharmacy, and OR supplies. Results: The study cohort included 5, 623 patients undergoing tympanostomy tube placement by 67 surgeons. Mean cost per surgery was 769 ± 3. Significant variations ( P < 0.001) in mean cost per procedure were identified by hospital (range 1212 ± 38 to 509 ± 11) and by surgeon (range 1330 ± 75 to 660 ± 11). Operating room and SDS preoperative were the greatest expenditures; each category accounted for over 30% of overall costs. Pharmacy costs and OR costs were some of the major drivers of cost variation among surgeons. Conclusion: This study demonstrates that OR and SDS preoperative costs accounted for the greatest expenditure in tympanostomy tube placement, and significant variation exists among surgeons and hospitals within a multihospital network. Further research is needed to elucidate factors accounting for such variation in cost and the overall impact on patient outcomes. Level of Evidence: 4. Laryngoscope, 126:1935–1939, 2016